Beetles as Model Organisms in Physiological, Biomedical and Environmental Studies – A Review - Adamski, Zbigniew; Bufo, Sabino A.; Chowański, Szymon; Falabella, Patrizia; Lubawy, Jan; Marciniak, Paweł; Pacholska-Bogalska, Joanna; Salvia, Rosanna; Scrano, Laura; Słocińska, Małgorzata; Spochacz, Marta; Szymczak, Monika; et al. (Frontiers in Physiology, 2019)
Model organisms are often used in biological, medical and environmental research. Among insects, Drosophila melanogaster, Galleria mellonella, Apis mellifera, Bombyx mori, Periplaneta americana or Locusta migratoria are often used. However, new model organisms still appear. In recent years, more and more insect species have been suggested as model organisms in life sciences, due to their worldwide distribution, environmental significance, the possibility of extrapolating research studies to vertebrates and relatively low cost of rearing. Beetles, as the largest insect order with their representative — Tribolium castaneum — first species with completely sequenced genome, seems to emerge as a new potential candidates for model organisms in various studies. Apart from Tribolium castaneum also species representing various Coleoptera families, such as Nicrophorus vespilloides, Leptinotarsa decemlineata, Coccinella septempunctata, Poecilus cupreus, Tenebrio molitor and many others are used. They are more and more often included in two major research aspects: biomedical and environmental studies. Biomedical researches focus mainly on unravelling mechanisms of basic life processes, such as feeding, neurotransmission or activity of the immune system, as well as on elucidating the mechanism of different diseases (neurodegenerative, cardiovascular, metabolic or immunological) using beetles as models. Furthermore, pharmacological bioassays for testing novel biologically active substances in beetles are also developed. It should be emphasized that beetles are a source of compounds with potential antimicrobial and anti-cancer activity. Environmental based studies focus mainly on the development and testing new potential pesticides, both of chemical and natural origin. On the other hand, beetles are used as food or its valuable supplements. Different beetle families are also used as bioindicators. Another important research concern beetles as models in behavioural ecology studies, for instance parental care. In this paper, we review current knowledge regarding beetles as model organisms and their practical application in various fields of life sciences.